Towards implementation of robust monitoring technologies alongside freshwater improvement policy in Aotearoa New Zealand. Issue 132 (June 2022) - Westerhoff, Rogier; McDowell, Richard; Brasington, James; Hamer, Mark; Muraoka, Kohji; Alavi, Maryam; Muirhead, Richard; Lovett, Abigail; Ruru, Ian; Miller, Blair; Hudson, Neale; Lehmann, Moritz; et al.
Abstract: International studies point out that some freshwater policy objectives are not achieved. This study describes that this is in part caused by shortcomings that include: the lack of targeted monitoring schemes to measure impact; a too small range of specific technologies rather than a wider suite of integrated multiple technologies; a too tight focus on sub-sets of stakeholders instead of the involvement of the wider range of end users; and poor trust building and technology explanations to end users. As an example, the New Zealand government is addressing widespread concern over the deterioration of the national freshwater resource by supporting a diverse portfolio of land and riparian management actions. Efforts to assess the effectiveness of these interventions and establish an evidence-based framework for future policies are however limited by the existing regional-scale freshwater monitoring infrastructure. Such hydrometric networks were established largely to assess the broader-scale regional 'state' of the environment and are generally out-of-phase with freshwater improvement actions that are implemented more typically at edge-of-field, farm or sub-catchment scales. Recent and rapid evolution in sensor technologies have created new opportunities to deliver information tuned to the appropriate parameters and frequencies needed to evaluate improvement actions. Despite this, the necessary transformative change in freshwater monitoring has yet to gather pace. In this study we explore barriers and solutions with the objective to better understand what is needed for successful integration of innovative monitoring technologies in a transitional environmental policy setting, using recent New Zealand policy directives as a case study. We use expert surveys and scenario testing to explore barriers to adoption to more robust and comprehensive monitoring required to establish the success, or otherwise, of freshwater improvement actions. This process reveals that rather than further innovations in technology, change in the practice of environmental monitoring is limited instead by the development of defensible and accepted guidelines on the application and effective deployment of existing sensors and methods. We demonstrate that improved knowledge exchange between engineers, scientists and practitioners can be addressed and propose a new decision support and communication tool to enable the selection of monitoring technologies and solutions fit-for-purpose to evaluate freshwater improvement outcomes on multiple scales involving multiple stakeholders.